2014
DOI: 10.1007/s00192-014-2463-1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study of lower urinary tract symptoms before and after surgical removal of a large pelvic mass

Abstract: This study provides evidence that the majority of LUTS present preoperatively improve significantly or resolve completely following removal of a ≥ 7-cm pelvic mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…A prospective case‐control survey followed 40 women with symptomatic fibroids for 1 year after surgical intervention and documented improvement in condition‐specific questionnaire scores for urinary function. Another small prospective observational study of 29 women showed a similar mean reduction of urinary symptoms on the UDI short form by 66% after removal of any pelvic mass (including fibroids) greater than 7 cm at preoperative ultrasound (U/S) assessment . In our study, all types of debulking procedures produced a similar improvement in urinary symptoms.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A prospective case‐control survey followed 40 women with symptomatic fibroids for 1 year after surgical intervention and documented improvement in condition‐specific questionnaire scores for urinary function. Another small prospective observational study of 29 women showed a similar mean reduction of urinary symptoms on the UDI short form by 66% after removal of any pelvic mass (including fibroids) greater than 7 cm at preoperative ultrasound (U/S) assessment . In our study, all types of debulking procedures produced a similar improvement in urinary symptoms.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, 96.6% of women presenting for surgical management of fibroids had a bothersome bladder symptoms. This is higher than previously reported and likely due to the high sensitivity of our detailed questionnaire.…”
Section: Discussioncontrasting
confidence: 64%
“…11 Two studies (n=145) reported on IIQ-7 scores after uterine artery embolization, 23,29 two (n=424) after high-intensity focused ultrasonography, 27,28 and three after hysterectomy or surgical intervention (n=173). 23,26,30 Overall, there was an improvement in mean score after intervention (summary mean change in score −10.7, 95% CI −15.8 to −5.6, I 2 =69%) (Fig. 3).…”
Section: Resultsmentioning
confidence: 94%
“…Six studies of moderate-to-high quality reported on change in IIQ-7 score after intervention, including one RCT and five single-arm studies (Appendix 2, http://links.lww.com/AOG/D227) 23,26–30 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…To determine what issues should be addressed in a survey for patients with sacral tumors, we hypothesized the existence of six domains based on the current literature: mental health, physical health, pain, gastrointestinal symptoms, sexual function, and urinary incontinence [6, 7, 27, 36, 39, 41, 45]. To assess content validity, we contacted 80 patients (of whom 32 responded, i.e.…”
Section: Methodsmentioning
confidence: 99%